HIERARKI KEBUTUHAN DAN KARAKTERISTIK PENGAKTUALISASI DIRI TOKOH REZA DALAM NOVEL JERITAN MALAM KARYA META MORFOSIS - Khalda Chairunnisa (Prosiding Seminar Nasional Sasindo, 2022)
The research "Hierarchy of Needs and Characteristics of Self-Actualization of Reza's Character in the Novel Jeritan Malam by meta.morfosis" aims to describe the forms of Maslow's hierarchy of needs fulfilled by Reza's character and to describe the form of Reza's character's self-actualization characteristics. The theory used in this study is Maslow's theory of the hierarchy of needs and characteristics of self-actualization. The method used in this research is using qualitative descriptive technique. For data collection techniques will be used literature study techniques and will be analyzed in detail for each presentation. The results obtained are that Reza's character has succeeded in fulfilling his hierarchy of needs, namely the physiological needs of Reza's character have been maximally obtained, security needs have been fulfilled, he has obtained the need for love and a feeling of belonging, the need for respect has been obtained by Reza's character, and the need for self-actualization has been carried out by Reza's character. The characteristics seen in Reza's character as a form and proof of his self-actualization are problem-centered, independence, interpersonal, seeing reality efficiently, autonomy, and acceptance of oneself and others as they are.Keywords: Maslow, Hierarchy of needs, Characteristics, Self-actualization.